2012
DOI: 10.1152/ajpheart.00940.2011
|View full text |Cite
|
Sign up to set email alerts
|

Role of connexin-43 in protective PI3K-Akt-GSK-3β signaling in cardiomyocytes

Abstract: Sarcolemmal connexin-43 (Cx43) and mitochondrial Cx43 play distinct roles: formation of gap junctions and production of reactive oxygen species (ROS) for redox signaling. In this study, we examined the hypothesis that Cx43 contributes to activation of a major cytoprotective signal pathway, phosphoinositide 3-kinase (PI3K)-Akt-glycogen synthase kinase-3β (GSK-3β) signaling, in cardiomyocytes. A δ-opioid receptor agonist {[d-Ala(2),d-Leu(5)]enkephalin acetate (DADLE)}, endothelin-1 (ET-1), and insulin-like growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…A recent study describes that interference with Akt1 signaling in all cells in vivo, reduced cardiac dysfunction, hypertrophy and cardiac fibrosis, thereby improving survival in a mouse model of spontaneous myocardial infarction ( Kerr et al, 2013). Most relevant for our study here is that Cx43 was shown to contribute to the activation of the PI3K/Akt signaling pathway in cardiac myocytes (Ishikawa et al, 2012).…”
Section: Novel Role Of Vcl In Pi3k/akt Signalingmentioning
confidence: 83%
“…A recent study describes that interference with Akt1 signaling in all cells in vivo, reduced cardiac dysfunction, hypertrophy and cardiac fibrosis, thereby improving survival in a mouse model of spontaneous myocardial infarction ( Kerr et al, 2013). Most relevant for our study here is that Cx43 was shown to contribute to the activation of the PI3K/Akt signaling pathway in cardiac myocytes (Ishikawa et al, 2012).…”
Section: Novel Role Of Vcl In Pi3k/akt Signalingmentioning
confidence: 83%
“…It also has been suggested that mitochondrial connexin-43 translocates to IMM through the HSP90-dependent translocase complex of the outer mitochondrial membrane (TOM) pathway (36) and plays a crucial role in cardioprotection associated with the PI3K/Akt/GSK-3β pathways (55). In PDE3B −/− heart the improved postischemic recovery of RPP was inhibited significantly by blocking the PKAdependent mitoK Ca channel opening by paxilline (Fig.…”
Section: Studies With Pde3amentioning
confidence: 88%
“…RNA was extracted from tissue samples and analyzed as previously reported (9,35). In brief, Endo and Epi tissues were carefully sampled with sharp scissors in cold (4°C) Tyrode solution in a refrigerator room.…”
Section: Methodsmentioning
confidence: 99%